Polarisierte Städte: Die AfD im urbanen Kontext. Eine Analyse von Wahl- und Sozialdaten in sechzehn deutschen Städten - Geilen, Jan Lucas; Mullis, Daniel (Copernicus Publications, 2021)
For the first time since 1945, with the Alternative für Deutschland (AfD) a far-right party has now consolidated itself in Germany on all political scales. In the political sciences as well as sociology, but not so much in human geography, there is much debate on the funding reasons. The debate is polarized and unfolds between two positions: on the one hand economic factors are marked as principal forces, on the other a cultural backlash. Electoral analyses have focused on the spatial division of the AfD's success between urban and rural areas as well as West and East Germany. By contrast, we focus on urban divisions. We examine the AfD's results in the general election of 2017 on the scale of districts in the largest city of each federal state by analyzing the correlation of the share of AfD votes with social data. In contrast to the polarized debate in the social sciences we choose a multidimensional perspective and analyze social data related to class, migration, acceptance of democracy and age. First, the resulting picture is heterogeneous across the cities and does not show a pronounced East-West polarization. Second, economic factors as well as factors related to migration correlate with the share of the AfD, whereby the former are pronounced somewhat stronger. Third, lack of trust in democracy is the most uniform indicator for a strong showing of the AfD in our sample; and fourth, in all cities there are districts which run counter to the generalized picture. We can show that in urban settings it is primarily, but not exclusively, in marginalized districts that the AfD has its strongholds. But this does not mean that all marginalized districts are dominated by the far-right party. In order to better understand the spatially highly fragmented social processes, in particular more qualitative research is needed.
Keywords: Wahlverhalten; Politik; Bundestagswahl; Wahlergebnis; Partei; Polarisierung; Stadtanalyse; Bevölkerungsstruktur